Expanded geographic distribution and dietary strategies of the earliest Oldowan hominins and Paranthropus - Plummer, TW; Oliver, JS; Finestone, EM; Ditchfield, PW; Bishop, LC; Blumenthal, SA; Lemorini, C; Caricola, I; Bailey, SE; Herries, AIR; Parkinson, JA; Whitfield, E; et al. (American Association for the Advancement of Science, 2023)
The oldest Oldowan tool sites, from around 2.6 million years ago, have previously been confined to Ethiopia's Afar Triangle. We describe sites at Nyayanga, Kenya, dated to 3.032 to 2.581 million years ago and expand this distribution by over 1300 kilometers. Furthermore, we found two hippopotamid butchery sites associated with mosaic vegetation and a C4 grazer-dominated fauna. Tool flaking proficiency was comparable with that of younger Oldowan assemblages, but pounding activities were more common. Tool use-wear and bone damage indicate plant and animal tissue processing. Paranthropus sp. teeth, the first from southwestern Kenya, possessed carbon isotopic values indicative of a diet rich in C4 foods. We argue that the earliest Oldowan was more widespread than previously known, used to process diverse foods including megafauna, and associated with Paranthropus from its onset.